GE_GERICHTE P/4683/2016 vom 7. Dezember 2016 - GE Cour de justice (2016)
RÉVISION(DÉCISION) ; MOTIF DE RÉVISION ; DÉCISION D'IRRECEVABILITÉ ; FRAIS DE LA PROCÉDURE | CPP.410; CPP.411; CPP.412; CPP.428